HUBUNGAN FAKTOR LINGKUNGAN DAN PERILAKU KELUARGA DALAM PENCEGAHAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU KECAMATAN TEMBALANG KOTA SEMARANG - Vandi Putra Malau; Nurjazuli Nurjazuli; Onny Setiani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that is caused by dengue virus and is transmitted by Aedes aegypty that can cause death especially in children. Dengue Hemorrhagic Fever (DHF) still becomes health problem, in 2013 Incidence Rate in sub-district Tembalang reached 218.20 per 100,000 people. Kedungmundu health center is one of the endemic areas with Incidence Rate 259.39 per 100,000 people. The spread of Dengue Hemorrhagic Fever (DHF) disease is influenced by low rate of Larva-Free Index (LFI) as a result it can increase cases of Dengue Hemorrhagic Fever (DHF). The purpose of this research is to know the relation of environmental factors and family behavior in preventing incident of Dengue Hemorrhagic Fever (DHF) in the Working area of Kedungmundu Health Center Temabalang sub-district Semarang. This Research was observational with design case-control. Samples (case) were all dengue fever patients that were recorded in the A Health Center Kedungmundu at the end of 2013, and samples (control) were people who were around dengue fever patients who do not suffer from Dengue Hemorrhagic Fever (DHF) at the end of 2013. Based onfromCountainerIndex (CI) thatcase group30.0% greater than thecontrol group is21.7% andin term of LFIhas notreachedmore than95% in the cases group with value of50.0%andthe control groupwith value of60.5%. While familybehavior in preventionhas not been optimalizedtothe EMB(Eradication of Mosquito Breeding) based on larvaldensityHIandCI≥ 5% and≥20% of BIvaluehas not been reached. So thereis still ariskof transmissionof dengue diseasein working area of Kedungmundu health center. Analysis of data using tests chi-square with equal significance p-value<0.05. Results of the study showed that there was no relation between environmental factorsandbehavior of the family.